P241 CARDIAC INVOLVEMENT IN CREATINE DEFICIENCY SYNDROME. (18th May 2022) - Del Franco, A; Battini, R; Kusmic, C; Forini, F; L' Abbate, S; Masotti, S; Musetti, V; Barison, A; Emdin, M; Vergaro, G
Abstract: Background: Previous reports have demonstrated electrocardiographic and echocardiographic abnormalities consistent with early–stage cardiomyopathy, in patients with creatine transporter deficiency (CRT–D), but cardiac involvement has never been accurately characterized. Our aim was to widen the current knowledge of the cardiac phenotype associated with creatine deficiency in a murine transgenic model and in patients with creatine deficiency syndrome (CDS). Methods: Wild type (n = 6) and transgenic CRT–/y mice (n = 6) were evaluated in vivo by electrocardiogram (EKG) and echocardiography for six months, and ex vivo by histological and biochemical analyses. Nine patients with CDS (4 with L–arginine:glycine amidinotransferase deficiency – AGAT–D, 5 with CRT–D) underwent blood samples, including cardiac biomarkers, EKG, Holter monitoring, echocardiography and cardiac magnetic resonance (CMR). Results: Compared to wild–type, CRT–/y mice showed a prolongation of QT interval (p = 0.008) (Fig. 1 ), as well as a trend of reduction of mitochondrial function (Fig. 2 ). No differences were dected in the left ventricular systolic function, in terms of ejection fraction and global longitudinal strain, at different times. Aldosterone levels were also not different between the two groups. Three patients with CDS also showed a prolonged QTc interval (median QTc 515 ms), while other 3 had a borderline QTc at Holter monitoring, without tachyarrhythmias. No subject had abnormal systolic and diastolic function. At CMR, an increase of native T1 value was reported in 4 subjects (median 1076 ms), 1 with an increase of extracellular volume matching with the detection of late gadolinium enhancement. Finally, 7 subjects with CDS presented with biohumoral signs of neurohormonal activation (2 with elevated renin, 1 with increased aldosterone and 4 with increased norepinephrine levels). Familiar carriers (3 for AGAT–D and 1 for CRT–D) showed no notable cardiac functional alterations, except for QTc prolongation in 2 AGAT–D carriers. Conclusion: Prolonged QT interval is observed in a murine model of CRT–D deficiency and in patients with CDS, in absence of an arrhythmic burden. No alterations in cardiac function were detected in the two setting, except for an increase of native T1 in patients with CDS suggesting an interstitial and replacement fibrosis.